Impotent Warriors : Perspectives on Gulf War Syndrome, Vulnerability and Masculinity - Kilshaw, Susie (Berghahn Books)
From September 1990 to June 1991, the UK deployed 53,462 military personnel in the Gulf War. After the end of the conflict anecdotal reports of various disorders affecting troops who fought in the Gulf began to surface. This mysterious illness was given the name (3z(BGulf War Syndrome(3y (B(GWS). This book is an investigation into this recently emergent illness, describing how the illness became a potent symbol for a plethora of issues, anxieties, and concerns. At present, the debate about GWS is polarized along two lines: there are those who think it is a unique, organic condition caused by Gulf War toxins and those who argue that it is probably a psychological condition that can be seen as part of a larger group of illnesses. With an anthropological focus on nuances and subtleties, the author provides a new approach to understanding GWS, one that makes sense of the cultural circumstances, specific and general, that gave rise to the illness.s
English
Keywords: Medical anthropology; Anthropology; medical anthropology; health and wellness; disease and society; social construction of illness; First Gulf War; social psychology; health scares; Masculinity; Semen; Vaccine